Linking Climate Change and Regional Economic Growth in Indonesia - Aulia, Ando Fahda; Iyan, Rita Yani; Kurniasih, Cut Endang (Department of Development Economics, Universitas Sriwijaya, 2025)
Weather factors have become a critical climate change issue at global forums because climate change can impact natural and human life, especially economic activities, as demonstrated by one of the examples of economic growth in a country. As a climate-vulnerable country, Indonesia experiences significant fluctuations in weather patterns, impacting key economic sectors, especially agriculture. Utilizing secondary data from 2014 to 2022, the study applies a panel data regression model to examine the relationship between climate and Gross Regional Domestic Product (GRDP) per capita growth as a proxy of regional economic growth. The findings revealed that rainfall and average air temperature have a negative sign and significantly affect economic growth, particularly in natural-resource-dependent sectors. The population growth rate also has a negative sign and significant influence on GRDP per capita dynamics, underscoring the need for enhanced economic capacity to match demographic changes. These findings provide valuable insights for policymakers to incorporate climate considerations into sustainable economic planning, especially for climate-sensitive sectors.